Estimate of an environmental magnetic field of fast radio bursts. (March 2016) - Lin, Wei-Li; Dai, Zi-Gao
Abstract: Fast radio bursts (FRBs) are a type of newly-discovered transient astronomical phenomenon. They have short durations, high dispersion measures and a high event rate. However, due to unknown distances and undetected electromagnetic counterparts at other wavebands, it is difficult to further investigate FRBs. Here we propose a method to study their environmental magnetic field using an indirect method. Starting with dispersion measures and rotation measures (RMs), we try to obtain the parallel magnetic field component B ̅‖ which is the average value along the line of sight in the host galaxy. Because both RMs and redshifts are now unavailable, we demonstrate the dependence of B ̅‖ on these two separate quantities. This result, if the RM and redshift of an FRB are measured, would be expected to provide a clue towards understanding an environmental magnetic field of an FRB.